O zambê é nossa cultura: o coco de zambê e a emergência étnica em Sibaúma, Tibau do Sul-RN - Lins, Cyro Holando de Almeida (2009)
The coco de zambê is a dance of which origin is credited to old slaves who inhabited the coastalregion of Rio Grande do Norte. The zambê appears intensely in the narratives related to the past and present of Sibaúma, a quilombola community located in the southern coast of the state. It is conceived as a sign of ethnicity linked to a local black ancestry. The group is known as "remnant of Quilombo," and is demanding the process of territorial settlement, as guaranteed through the Brazilian federal constitution. The coco de zambê, presented as a kind of "certificate of ancestry to the group, besides, after a long period of abandonment, the dance is beeing "revitalized" and exploited by a part of the group alongside the demands for recognition. In this process there are several interlinked actors: NGOs, state agencies to promote the culture, representatives of public authorities and local leaders. Here, I'm interested in understanding how this process of revival occurs with the coco de zambê in Sibaúma: how a "brincadeira" (play) of the ancients comes to be a "cultural reference" and a means of political mobilization concerning their recognition